FungiSync: Merging Cyberdelic Mixed Realities - Hu, Botao Amber; Huang, Danlin; Tao, Yilan Elan; Hu, Xiaobo Aaron; Lin, Rem Rungu (Association for Computing Machinery, 2025)
FungiSync is a somaesthetic mixed reality participatory ritual inspired by cyberdelic culture and fungal wisdom, exploring collective intersubjectivity through asymmetric mixed reality merging or swapping. Participants hold masquerade-style, mushroom-decorated masks, each featuring a distinct, audio-reactive psychedelic augmented reality overlay—underscoring how technology-mediated realities can become asymmetrical and "techno-autistic". Traditional social protocols, such as handshakes, have been reprogrammed—upon bodily contact, these mixed realities merge or swap, mirroring fungi’s collaborative resource exchange. This process blurs the boundaries between individuals and dissolves binary perspectives between "you" and "me". FungiSync exposes the impact of technology-mediated asymmetries while proposing an alternative: fostering a non-dualistic discourse that echoes fungal interdependence.
Keywords: elan-tao